2021
DOI: 10.1063/5.0049111
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning on neutron and x-ray scattering and spectroscopies

Abstract: Neutron and X-ray scattering represent two state-of-the-art materials characterization techniques that measure materials' structural and dynamical properties with high precision.These techniques play critical roles in understanding a wide variety of materials systems, from catalysis to polymers, nanomaterials to macromolecules, and energy materials to quantum materials. In recent years, neutron and X-ray scattering have received a significant boost due to the development and increased application of machine le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 209 publications
1
63
0
Order By: Relevance
“…It was demonstrated that X-ray analytical data could be converted to a crystalline structure. 19 For example, XANES spectra were used to obtain the atomic arrangement. 20 This indicates that the analytical data could include the structural and physical features of materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that X-ray analytical data could be converted to a crystalline structure. 19 For example, XANES spectra were used to obtain the atomic arrangement. 20 This indicates that the analytical data could include the structural and physical features of materials.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the development of a number of approaches aimed at exploiting machine learning for data reduction, prediction, and/or analysis, in addition to accelerating theoretical calculations of electronically-excited states and spectra. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In particular, and the focus of this Article, the X-ray regime provides valuable element-and site-specific information on the geometric, electronic, and spin structure of matter and, consequently, a number of recent works have addressed directly the development of models for the prediction and analysis of X-ray absorption spectra. These approaches can be subdivided into two categories: (i) ''forward'' (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by [14] provides an overview of machine learning activities for neutron scattering at ORNL, which hosts the SNS. Similarly, machine learning applications for neutron and x-ray scattering and spectroscopy research were highlighted by [15]. Lastly, the recent review paper by [16] highlights the machine learning research on the broader field of nuclear physics, which includes a section on surrogate modeling with machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%